La multiplication rapide du bananier et du plantain au Cameroun - Bonte, E.; Verdonck, R.; Grégoire, L. (Tropicultura, 1995)
Rapid Multiplication of Banana and Plantain Trees in Cameroon. To increase the rate of multiplication of banana and plantain trees, several technics are practiced. Less sophisticated than tissue culture which necessitates a laboratory, this note presents two types of rapid multiplication practices : 1 ° by removal of the apical dominance, that is decapitation, bending over and false decapitation. 2° by spliting of corms and buds.